Cape Verde : Staff Report for the 2005 Article IV Consultation, Sixth Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2005 Article IV Consultation for Cape Verde focuses on economic developments and fiscal policy. The fiscal deficit was lower than expected, and reserve accumulation exceeded the programmed level. Cape Verde appears well positioned to attract increasing external support, and there is also scope to mobilize greater domestic resources. In this regard, improvements in tax administration and rationalization of exemptions would enhance improvements to the revenue base that have come about with the new VAT.